The relationship model between life expectancy at birth tuberculosis and PM2.5 developing and developed countries in Asia - Hasnawati, Sri; Usman, Mustofa; Russel, Edwin; Othman, Raihan (Edelweiss Applied Science and Technology, 2025)
Studies on environmental conditions, the health of a country’s population, and life expectancy at birth (LEB) have attracted the attention of many researchers and raised awareness among governments in both developed and developing countries to improve the environment, such as reducing air pollution levels. Research examines the pattern of association between PM2.5 pollution levels and tuberculosis (TB) disease in both developed and developing countries in Asia. This study analyzes the relationship between pollution levels caused by PM2.5 and TB disease against LEB in these countries. The relationship model built between PM2.5, TB, and LEB is a linear model with dummy variables for developed and developing countries. The results showed that the relationship between PM2.5 and TB is significant; namely, the higher the PM2.5, the higher the TB cases in both developed and developing countries in Asia. The relationship between PM2.5 and TB with LEB is also significant, with a negative pattern: the lower the PM2.5 levels and the fewer TB cases in a country, the higher the LEB level, indicating better environmental conditions.